The trace fossil Polykampton recurvum n. isp. (sequestrichnia) from the Maastrichtian–Paleocene deep-sea deposits of NW Italy. (November 2021) - Uchman, Alfred; Rattazzi, Bruno
Abstract: Polykampton recurvum n. isp. is the sixth ichnospecies of the ichnogenus Polykampton Ooster, 1869 . It is a horizontal structure composed of a median cylindrical tunnel and narrow, usually back-curved lateral lobes located in alternating position. It occurs 2–3 cm below the top of single beds in the Maastrichtian–Paleocene deep-sea turbiditic marlstones of the Monte Antola Unit in the Northern Apennines. The lobes of P. recurvum n. isp. are actively filled with gray mudstone from above through the permanently open median tunnel. The trace fossil belongs to the category sequestrichnia, which is typical of oxygenated deep-sea environments characterized by seasonal or episodic supply of organic matter into a generally oligotrophic environment. P. recurvum n. isp. was produced by a "worm, " probably a polychaete, which adapted to seasonal or only episodic supply of organic matter to the deep-sea floor. The tracemaker stored the organic-rich mud in the lobes for nutrition during times of low organic matter availability on the seafloor. UUID: http://zoobank.org/49555117-1c39-4658-8b49-3f3e2f47ba27